Increased coagulation and suppressed generation of activated protein C in aged mice during intra-abdominal sepsis - Starr, Marlene E. (Am J Physiol Heart Circ Physiol, 2014)
Sepsis is a life-threatening clinical condition that is particularly serious among the elderly who experience considerably higher mortality rates compared with younger patients. Using a sterile endotoxemia model, we previously reported age-dependent mortality in conjunction with enhanced coagulation and insufficient levels of anti-coagulant factor activated protein C (aPC). The purpose of the present study was to further investigate the mechanisms for age-dependent coagulation and aPC insufficiency during experimental sepsis. Intra-abdominal sepsis was induced by cecal ligation and puncture (CLP) using 21 or 16 gauge (G) needles (double-puncture) on young (4 to 6 mo old) and aged (20 to 25 mo old) male C57BL/6 mice. When compared with young mice, aged mice showed significantly increased mortality (92% vs. 28%), systemic inflammation, and coagulation in the lung and kidney after 21G CLP. Young mice with more severe CLP (16G) showed a mortality rate and inflammation equivalent to aged mice with 21G CLP; however, enhanced coagulation and kidney dysfunction were significant only in the aged. In young mice, increased levels of aPC after CLP were coupled with reduced levels of protein C (PC), suggesting the conversion of PC to aPC; however, PC and aPC levels remained unchanged in aged mice, indicating a lack of PC to aPC conversion. Activation of fibrinolysis, determined by plasma d-dimer levels, was similar regardless of age or CLP severity, and plasminogen activator inhibitor-1, an inhibitor of fibrinolysis, showed severity-dependent induction independent of age. These results suggest that enhanced coagulation in aged mice during sepsis is due to dysfunction of the PC activation mechanism.